When and How to Provide Feedback and Instructions to Athletes?—How Sport Psychology and Pedagogy Insights Can Improve Coaching Interventions to Enhance Self-Regulation in Training - Otte, Fabian W.; Davids, Keith; Millar, Sarah-Kate; Klatt, Stefanie (Frontiers in Psychology, 2020)
In specialist sports coaching, the type and manner of augmented information that the coach chooses to use in communicating and training with individual athletes can have a significant impact on skill development and performance. Informed by insights from psychology, pedagogy, and sport science, this position paper presents a practitioner-based approach in response to the overarching question: When, why, and how could coaches provide information to athletes during coaching interventions? In an ecological dynamics rationale, practice is seen as a search for functional performance solutions and augmented feedback is outlined as instructional constraints to guide athletes’ self-regulation of action in practice. Using the exemplar of team sports, we present a skill training communication model for practical application in the context of the role of a specialist coach, using a Constraints-Led Approach. Further based on principles of a Nonlinear Pedagogy, and using the recently introduced ‘Periodization of Skill Training’ (‘PoST’) framework, the proposed model aims to support practitioners’ understanding of the pedagogical constraints of feedback and instruction during practice. In detail, the ‘PoST’ framework’s three skill development and training stages work to 1) directly impact constraint manipulations in practice designs; and 2) indirectly affect coaches’ choices of external (coach-induced) information. In turn, these guide practitioners on how to and when to apply different verbal instruction methodologies and aims to support the design of effective skill learning environments. Finally, several practical guidelines in regard to sports coaches’ feedback and instruction processes are proposed.